Struktur Komunitas Moluska di Perairan Pantai Grand Bali Beach Sanur, Bali - I Bagus Andreana Surya Nugraha; Pande Gde Sasmita Julyantoro; Suprabadevi Ayumayasari Saraswati (Current Trends in Aquatic Science, 2018)
The purpose of this research was to investigate the community structure of mollusks, water quality and substrate type at Grand Bali Beach, Sanur. The research location was divided into 4 stations. This research was held in January until February 2018. The data was obtained from transect 1x1 m. The research was analysis by descriptive quantitative method. The research found about 33 species. The total abudance from station 1, 2, 3 and 4 were 5,75 ind/m2, 6 ind/m2, 6 ind/m2 and 9 ind/m2 respectively. The value of diversity was 2-2,52, indicated a moderate diversity while the evenness was 0,8-0,9, that indicated the high evenness and the dominance was low about 0,11-0,19. The community structure of mollusk at the Grand Bali Beach Sanur was still in normal condition for mollusk that supported by good water quality and favorable substrate type.